Lifestyle Factors Associated with Metabolic Syndrome Z-Score in US Adolescents. (29th May 2020) - Summer, Suzanne; Jenkins, Todd; Inge, Thomas; Deka, Ranjan; Khoury, Jane
Abstract: Objectives: Metabolic syndrome (MetS) is a cluster of abnormalities including abdominal obesity that increases risk for diabetes and cardiovascular disease. MetS affects ∼10% of US adolescents, but more may be at risk. The MetS severity z-score (MetS-z) is a continuous measure that may be useful for indicating MetS risk. Preventing at-risk adolescents from developing MetS may be achievable through changes in lifestyle factors such as diet and physical activity. Our objective was to evaluate the relationship of lifestyle-related factors with MetS-z in adolescents. Methods: We performed a cross-sectional analysis of adolescents (12 to 19 y) from the National Health and Nutrition Examination Survey (NHANES) 2011–2016. MetS-z was calculated from sex- and race-specific equations developed for adolescents. Sagittal Abdominal Diameter (SAD, representing abdominal visceral fat) was obtained using NHANES standard procedures. Dietary intake was estimated via two 24-hour diet recall interviews and used to calculate the Healthy Eating Index (HEI)-2015 total (range 0–100) and component scores (range 0–10) indicating diet quality. Physical activity (PA, minutes/week of voluntary moderate or vigorous exercise) was reported by participants to trained interviewers and used to determine adherence to national PA guidelines of at least 60 min/day. Multivariable linear regression was used to evaluate the relationship of HEI scores, SAD and physical activity with MetS-z. Results: Sample size was 1291 (49% female, 50% white) adolescents. Means (SEM) were: Age, 15.4 y (0.09); BMI z-score, 0.63 (0.04); MetS-z, −0.08 (0.03); SAD, 18.3 cm (0.14); and HEI score, 47.4 (0.46). Median min/week of PA was 178.5, with 30.4% of adolescents meeting PA guidelines. The final model (R 2 = 0.53) included age, SAD (β = 0.17, P < 0.0001), HEI score (β = −0.003, P = 0.09), and physical activity (β = −0.005, P = 0.69). Conclusions: US adolescents consume a poor-quality diet and less than half meet physical activity guidelines, yet as a group they have a MetS z-score <0, indicating low overall risk. SAD had a significant, positive association with MetS-z. While physical activity and diet were not significant in the model, results suggest the need for improvement of overall diet quality to potentially reduce risk of MetS and related chronic diseases in youth. Funding Sources: None.